CASHLESS GOVERNMENT: A CORRUPTION PREVENTION STRATEGY IN GOVERNMENT AGENCIES - Paramita Nur Kurniati; Bernardus Yuliarto Nugroho (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
The phenomenon of corruption cases continues to increase from year to year, both from the number of cases that occur and the amount of state financial losses incurred. The criminal acts of corruption committed are also increasingly systematic and massive in all aspects of society's lives. To respond to this phenomenon, the Government, in this case the Ministry of Finance, issued a